Communication Design Education Oriented Vocational Curriculum Framework - Rini Maulina (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
Without realizing it, our daily lives are filled with images, not only through the pictures plastered on billboards along the street, or through television and computer shows, but today everyone has their own screen in their hands. Advances in information technology have flooded us with information coming through the screens of our mobile phones. Behind the images we see on our cell phones is the enormous role of Communication Design. It is not surprising for us that currently Communication Design education is spreading in various cities throughout Indonesia, through various levels of education both Vocational, Bachelor, Master and Doctoral, it reflects that Communication Design education is needed in the era of information technology. Communication Design Education has a curriculum that is made to prepare personnel who can establish expertise and skills in the field of Communication Design ready to work and able to compete globally. Especially for vocational level communication design education, the curriculum must have a Link and Match with the Industrial World Business World (DUDI). The problem is whether the Frame work curriculum in the field of communication design at the vocational level in Indonesia is in accordance with the vocational curriculum framework. This is important to know in order to support the goals of vocational programs that can produce the latest innovations, trends, practical concerns, and can face challenges in the field of communication design at the vocational level. The research method uses descriptive, by analyzing the curriculum in the field of communication design at the vocational level in Indonesia through interviews, observations and literature studies. The results of the analysis found that most of the vocational curriculum frameworks are not in accordance with government policies through the Ministry of Education and Culture